The Effect of Financial Performance and Corporate Governance on Tax Avoidance in Manufacturing Companies listed on the Indonesia Stock Exchange 2015–2019 - J. Raudhatul; . Azwardi; S. Sa’adah (Модернизация, инновация, развитие, 2022)
Purpose: this study aims to study the effect of financial performance and corporate governance on tax avoidance in manufacturing companies listed on the Indonesia Stock Exchange in 2015–2019.Methods: financial performance and corporate governance as independent variables with financial performance indicators are ROA, ROE and Leverage while indicators of corporate governance are the board of commissioners, audit committee and external audit quality. Tax avoidance as the dependent variable was measured by using ETR (effective tax rate). This research uses purposive sampling to get a sample size of 60 companies around 5 years and use common effect panel data regression analysis. The data in this study were analyzed with Eviews 9.0.Results: (1) Financial Performance as measured by ROA, ROE and leverage. ROA and leverage has an indication on tax avoidance while ROE has no an indication on tax avoidance in listed manufacturing companies on the IDX in 2015-2019. (2) Corporate Governance as measured by the board of commissioners, audit committee and external audit quality shows that has an indication on tax avoidance in listed manufacturing companies on the IDX in 2015–2019.Conclusions and Relevance: the results of the study prove that ROA, leverage, the board of commissioners, audit committee and external audit quality have a significant and significant effect on tax avoidance, but the ROE variable has no significant effect on tax avoidance in listed manufacturing companies on the IDX in 2015–2019.